1998
DOI: 10.1093/brain/121.1.91
|View full text |Cite
|
Sign up to set email alerts
|

What is straight ahead to a patient with torticollis?

Abstract: Vestibular and neck proprioceptive signals are known to be used in judging the locations of objects in space and relative to the body. Given that these signals are asymmetric in patients with spasmodic torticollis, one would expect such patients to have abnormal spatial perception. We tested this idea by measuring patients' perception of visual straight ahead (VSA) under various conditions: with the body in its primary position, i.e. with the head and trunk as closely aligned as possible, and after well define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 0 publications
7
35
0
Order By: Relevance
“…2). These results are consistent with prior studies showing the importance of proprioceptive feedback for head control (Smetanin et al, 1993;Anastasopoulos et al, 1998;Bove et al, 2004Bove et al, , 2007Malmström et al, 2009). There are several reasons the head integrator may depend on proprioception.…”
Section: Ocular Versus Head Neural Integratorssupporting
confidence: 93%
See 2 more Smart Citations
“…2). These results are consistent with prior studies showing the importance of proprioceptive feedback for head control (Smetanin et al, 1993;Anastasopoulos et al, 1998;Bove et al, 2004Bove et al, , 2007Malmström et al, 2009). There are several reasons the head integrator may depend on proprioception.…”
Section: Ocular Versus Head Neural Integratorssupporting
confidence: 93%
“…Most healthy subjects show subtle end-gaze nystagmus in the dark, a phenomenon attributed to an imperfect ocular integrator and its reliance on visual feedback (Jürgens et al, 1981;Pastor et al, 1994;Abadi and Scallan, 2001; Leigh and Zee, 2006). Patients with cerebellar disease and monkeys with lesions of the cerebellum show enhanced gaze-evoked nystagmus (Zee et al, 1980(Zee et al, , 1981.…”
Section: Ocular Versus Head Neural Integratorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies of visuospatial perception in patients with spasmodic torticollis [24]reported similar findings: measuring the patients’ visual perception under various conditions (with the body in its primary position and after passive rotations of the head and/or trunk) revealed symmetrical results independent of the direction of the torticollis. Accordingly, the authors concluded that it is unlikely that asymmetries in afferent inflow are responsible for the asymmetry of motor output in spasmodic torticollis.…”
Section: Discussionmentioning
confidence: 64%
“…Instead, they set the line to upright, on average, i. e. parallel to the midsagittal plane of their trunks [2]. Similarly, in a previous study in which we tested the subjective visual straight ahead (VSA) after rotations of the head and trunk, ST patients referenced it to their trunks, unlike normal subjects who use a head-centric frame of reference [3]. One could conclude that these findings reveal a direct correlate for an erroneous proprioceptive head-on-trunk signal.…”
Section: Introductionmentioning
confidence: 99%